Technology of sword blades from the La Tène period to the early modern age : the case of what is now Poland - Zabinski, Grzegorz, (Archaeopress Archaeology, 2014)
This text assesses the results of recent metallographic examination of 45 sword blades (mid-2nd century BC to early-16th century) from the territory of what is now Poland.